Distinguishing the offensive and defensive performances of starters and substitutes between high-level and low-level teams in elite women`s basketball games - Sun, W.; Kok, L. Y.; Chee, C. S.; Xiao, W. (PLOS ONE, 2025)
The primary goals of this study were to differentiate the offensive and defensive performances of starters and substitutes between high- and low-level teams in elite women`s basketball. This study examined 432 players from 36 women`s basketball teams who competed in the Tokyo Olympics, the 2022 Women`s Basketball World Cup, and the Paris Olympics. The rank-sum ratio was used to quantify and describe offensive and defensive performances of starters and substitutes, while the independent sample t-test, Pearson correlation, and Spearman Rho correlation were employed to test the differences and relationships between the various variables at a 0.05 level of significance. The results indicated that the offensive and defensive performances of both starters (r = 0.932) and substitutes (r = 0.848) had a significant correlation with the final rankings. Compared to high-level teams, low-level teams showed significant differences in points (p = 0.017), two-point (p = 0.015) and three-point (p = 0.000) shooting percentages, assists (p = 0.004), and steals (p = 0.040) for starters, as well as points (p = 0.033) and defensive rebounding (p = 0.027) for substitutes. Additionally, both starters and substitutes significantly correlated with points, two-point and three-point shooting percentages, defensive rebounds, and assists (r > 0.600).